Application of advanced real-time RRT and incremental backstepping control for rotary-wing unmanned aircraft systems - An, J.W.; Lim, M.G.; Choi, Y.S.; Woo, J.W.; Kim, C.J. (My University, 2022)
RRT is a well-known algorithm used for path and motion planning and exhibits good performance in generating a path quickly and efficiently. Many attempts were made to use these advantages for generating paths in real time; however, critical problems were observed when the algorithm was applied to aircraft. Unlike other mobile vehicles, aircraft require careful consideration of their limits, such as velocity, turn radius, and load factors. Only a few studies consider this; hence, in this study, we propose a method to consider important dynamic characteristics when planning paths in real time. The Advanced Real-Time RRT* algorithm suggested in this paper considers the limits by adopting the concept of “trajectory” as a new approach. A trajectory contains information on the location, velocity, and acceleration of an aircraft at each waypoint. If a trajectory is determined to be infeasible for flight, a different path is created and the path is converted to a new trajectory. In addition, the proposed algorithm was combined with a nonlinear controller called the incremental backstepping control, which is a robust controller having an excellent trajectory tracking performance. For validating the system, a series of simulations were conducted using a high-fidelity rotorcraft mathematical model as a system plant. Simulation results show that the proposed algorithm is sufficient for generating paths in a dynamic environment.